Integrated delivery of family planning and childhood immunisation services in routine outreach clinics: findings from a realist evaluation in Malawi - Jessie K. Hamon; Shari Krishnaratne; Jenna Hoyt; Misozi Kambanje; Shannon Pryor; Jayne Webster (BMC, 2020)
Abstract Background Family planning (FP) needs among postpartum women in low- and middle-income countries remain largely unmet. Integrating FP with childhood immunisation services could partially reduce this unmet need by creating multiple opportunities for timely contact with FP services during the 12 months following childbirth. Methods A realist evaluation of an intervention integrating FP and childhood immunisation services in routine outreach clinics in two rural districts of Malawi was conducted. A Context-Mechanism-Outcome (CMO) framework was used to describe the drivers of the intervention. A detailed programme theory was developed based on the analysis of semi-structured interviews and focus group discussions with 50 stakeholders. Results A total of 9 core mechanisms were identified, which centred on constructs of access. Findings revealed that on the demand side, women were motivated to attend outreach clinics due to shorter travel distances; they felt confident they could access FP services and use contraceptive methods covertly if needed; and when supported by their husband, they were empowered to take up the use of contraceptive methods. On the supply side, providers were empowered through the training they received to provide integrated services; they were confident in their ability to provide essential services; and they were motivated by teamwork and by the recognition they received for their work. Additionally, some providers were found to be unwilling to walk long distances to reach remote clinics, which was seen to negatively affect the availability of services. Conclusions The delivery of integrated FP and childhood immunisation services in the context of routine outreach clinics in rural Malawi was seen to trigger mechanisms of accessibility and to improve the acceptability and availability of FP services. However, further research is needed to understand how the integration of these services in a routine outreach clinic setting may affect other dimensions of accessibility, including the approachability, appropriateness and affordability of services.